History and electronic artefacts - Higgs, Edward (Oxford University Press, 1998)
We are now entering a world of electronic communications where an increasing amount of contemporary information is created and retained only in electronic form. How will such unstable flows of information be preserved for future historians? Will the future have a past? Will the history of our contemporary world be lost to our descendants? History and Electronic Artefacts is the first publication to examine the implications of this revolution for historical research...